Fluorescence resonance energy transfer-based analysis of cAMP dynamics in live neonatal rat cardiac myocytes reveals distinct functions of compartmentalized phosphodiesterases. - Mongillo, M; McSorley, T; Evellin, S; Sood, A; Lissandron, V; Terrin, A; Huston, E; Hannawacker, A; Lohse, M; Pozzan, T; Houslay, MD; Zaccolo, M (2004)
Cardiac myocytes have provided a key paradigm for the concept of the compartmentalized cAMP generation sensed by AKAP-anchored PKA. Phosphodiesterases (PDEs) provide the sole route for degrading cAMP in cells and are thus poised to regulate intracellular cAMP gradients. PDE3 and PDE4 represent the major cAMP degrading activities in rat ventriculocytes. By performing real-time imaging of cAMP in situ, we establish the hierarchy of these PDEs in controlling cAMP levels in basal conditions and on stimulation with a beta-adrenergic receptor agonist. PDE4, rather than PDE3, appears to be responsible for modulating the amplitude and duration of the cAMP response to beta-agonists. PDE3 and PDE4 localize to distinct compartments and this may underpin their different functional roles. Our findings indicate the importance of distinctly localized PDE isoenzymes in determining compartmentalized cAMP signaling.